2019
DOI: 10.1007/s10616-019-00296-4
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme from hen egg white ameliorates lipopolysaccharide-induced systemic inflammation in mice

Abstract: Lysozyme is an anti-bacterial protein that is widely distributed in nature. Our previous studies revealed that lysozyme shows anti-inflammatory effect on hyperinflammatory macrophages in vitro. The effect of lysozyme on lipopolysaccharide-induced inflammation model mice was examined in this study. Oral administration of lysozyme at 2250 mg/kg body weight/day (high-dose group) significantly suppressed interleukin (IL)-6 and tumor necrosis factor-a levels in the serum. IL-6 level in the spleen was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…An interesting development concerns the possibility to attribute to lysozyme additional functions, besides antibacterial defence, such as a potent anti-inflammatory activity [29,35,36]. Lysozyme significantly suppresses the production of the inflammatory cytokines TNF-α, IL-1β and IL-6 (Interleukin 6) [37,38,39], independently from muramidasic activity, because of the peptide motifs found in the N-terminal region of the protein [40]. Furthermore, Gallo et al [41] showed that lysozyme is able to prevent the production and release of inflammatory mediators, such as IL-6, and to reduce macrophage recruitment in the inflammatory site induced by AGE (advanced glycation endproducts) in HK-2 proximal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting development concerns the possibility to attribute to lysozyme additional functions, besides antibacterial defence, such as a potent anti-inflammatory activity [29,35,36]. Lysozyme significantly suppresses the production of the inflammatory cytokines TNF-α, IL-1β and IL-6 (Interleukin 6) [37,38,39], independently from muramidasic activity, because of the peptide motifs found in the N-terminal region of the protein [40]. Furthermore, Gallo et al [41] showed that lysozyme is able to prevent the production and release of inflammatory mediators, such as IL-6, and to reduce macrophage recruitment in the inflammatory site induced by AGE (advanced glycation endproducts) in HK-2 proximal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several other factors like the regulation of translation, protein turnover and the regulation of its activity by post-translational modifications, including the interaction with co-factors, can together modulate the biological activity of a protein without the appreciable involvement of modifications at the mRNA level. Furthermore, a very recent study conducted in mice with LPS-induced systemic inflammation reports the significant suppression of TNF-α protein levels in serum and spleen after oral administration of lysozyme but, in contrast TNF-α gene expression resulted correspondingly not affected [39].…”
Section: Discussionmentioning
confidence: 99%
“…[ 60 ]. Furthermore, it has been found that lysozyme from hen egg white ameliorates LPS-induced systemic inflammation in mice [ 61 ]. Sethi S et al showed that the treatment with oxidized EPA, but not native EPA, diminished LPS-induced surface expression of E-selectin, VCAM-1, and ICAM-1 in a dose dependent manner, suggesting an important role for oxidized metabolites of n-3 PUFAs [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that egg white lysozyme can inhibit both systemic and organ specific inflammation. 161 In the cecal ligation and puncture (CLP) induced inflammation in mice, lysozyme can reduce the release of HMGB1, leukocyte migration, and sepsis mortality and treat vascular inflammation by inhibiting the HMGB1 signaling pathway. 149 Lysozyme exhibits a concentration-dependent inhibitory effect on polyphosphate-mediated inflammation in mice and can inhibit polyp-mediated vascular barrier permeability, up-regulation of inflammatory biomarkers, leukocyte adhesion/migration, and activation and/or production of NF-κB, TNF-α, and IL-6.…”
Section: Anti-inflammatory Activity Of Egg Whitementioning
confidence: 99%